2017
DOI: 10.1002/cctc.201700299
|View full text |Cite
|
Sign up to set email alerts
|

Peptide‐FlgA3‐Based Gold Palladium Bimetallic Nanoparticles That Catalyze the Oxygen Reduction Reaction in Alkaline Solution

Abstract: Given the synergetic properties of different metal species, bimetallic nanoparticles are of immense scientific interest and technological importance in the field of catalysis. A peptide‐based method represents a new avenue to fabricate bimetallic nanocatalysts with a controllable size, shape, composition, and subtle surface microstructure. However, the electrocatalytic abilities of these peptide‐based bimetallic nanoparticles remain largely unexplored. Herein, we employed the peptide sequence FlgA3 to fabricat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 63 publications
(153 reference statements)
0
8
0
Order By: Relevance
“…For Pd 50 Ru 50 /CNs, the peak with a binding energy at 342.0 eV and 336.8 eV can be attributed to the Pd3d 3/2 and Pd3d 5/2 electrons, respectively [42]. The two peaks can be further deconvoluted into two pairs of doublets, and the peaks at the lower binding energies of 336.3 eV and 341.5 eV can be assigned to metallic Pd [36], while the peaks at higher binding energies of 337.6 eV and 343.1 eV are ascribed to the Pd (II) species [43,44]. This indicates the formation of palladium (II) oxides, which agree well with the Pd-carbon substrate hybrid systems in several previous reports [36,45,46].…”
Section: X-ray Diffraction (Xrd) and Xps Analysismentioning
confidence: 99%
“…For Pd 50 Ru 50 /CNs, the peak with a binding energy at 342.0 eV and 336.8 eV can be attributed to the Pd3d 3/2 and Pd3d 5/2 electrons, respectively [42]. The two peaks can be further deconvoluted into two pairs of doublets, and the peaks at the lower binding energies of 336.3 eV and 341.5 eV can be assigned to metallic Pd [36], while the peaks at higher binding energies of 337.6 eV and 343.1 eV are ascribed to the Pd (II) species [43,44]. This indicates the formation of palladium (II) oxides, which agree well with the Pd-carbon substrate hybrid systems in several previous reports [36,45,46].…”
Section: X-ray Diffraction (Xrd) and Xps Analysismentioning
confidence: 99%
“…In addition, the Pd4 peptide possesses a Pro at the seventh position. Due to the Pro , structure, this residue establishes a prominent kink within the biomolecule, limiting the degrees of rotation. This limited range of motion, coupled with binding of the metal ions at the His residues may limit the interaction of the Au 3+ ions with the reducing Trp residues, resulting in diminished reductive capabilities from the Pd4-based sequences.…”
Section: Results and Discussionmentioning
confidence: 99%
“…A method adapted from Li et al was followed for monometallic Au and Pd NP synthesis. 35 A 15 μL aliquot of a pre-prepared aqueous solution of either 0.1 M of HAuCl 4 ·3H 2 O or K 2 PdCl 4 was added to 4.94 mL of water containing 0.5 mL of 3.0 mM aqueous Pd4 peptide. After stirring the mixture for 30 min, the reaction process was initiated by adding 0.1 M NaBH 4 aqueous solution (45 μL, freshly prepared).…”
Section: Methodsmentioning
confidence: 99%
“…[27][28][29][30] Peptides composed of 7 to 12 amino acids, and engineered combinations of them, were used to generate different inorganic nanoparticles and bimetallic alloy NPs in aqueous solution under ambient conditions. [31][32][33][34][35] Previous studies have shown that the Pd4 enables the formation of uniform sized nanoparticles, without it, uniform nanoparticles do not form. 30,36 Herein we present an efficient, prompt, scalable, and biobased technique using biocombinatorially derived Pd4 peptide (TSNAVHPTLRHL) for the preparation of reusable bimetallic nanocatalysts containing Pd and Au for selective nitrite reduction into N 2 .…”
mentioning
confidence: 99%